5G ladder-type BAW filter design - Zhou, Haorong (Nanyang Technological University, 2021)
In the current telecommunication system, the number of electronic devices which want to access the network and transmit their data is climbing with a horrible speed. If the Internet of Things technology becomes dominant one day, this phenomenon will be more pronounced. Under the situation of a huge number of electronic devices accessing the network simultaneously, the interference between those electronic devices will definitely be much significant, therefore high-quality filters are required to help each electronic device to select the correct signal and refuse the interference signals. However, as the operating frequency is getting higher and higher, the traditional filters used in LF and MF bands are no longer suitable. People has found that the acoustic filters showed very good performances in and above VHF band, especially the Bulk Acoustic Filter (BAW). Therefore, this project has been carried out to design a good BAW filter, and the results have shown good performances, such as high central frequency, high channel selectivity, good OoB rejection and so on. Moreover, The commonly used BAW filter can be divided into two kinds: ladder and lattice. The designed BAW filter in this project is in ladder type, which can provide a higher selectivity due to the higher near-band rejection compared to the lattice type. The ladder type also has other strengths, and those will be introduced in details in this dissertation.